2020
DOI: 10.1029/2020jb019731
|View full text |Cite
|
Sign up to set email alerts
|

3‐D Magnetotelluric Imaging of the Easternmost Kunlun Fault: Insights Into Strain Partitioning and the Seismotectonics of the Jiuzhaigou Ms7.0 Earthquake

Abstract: We present a three‐dimensional electrical resistivity model of the crust and upper mantle beneath the easternmost Kunlun fault (EKLf), obtained by three‐dimensional inversion of magnetotelluric (MT) data. The crust of the Songpan‐Ganzi block is characterized by high resistivity from the surface to a depth of around 20 km, and by low resistivity in the mid‐lower crust in the depth range 20–40 km. The eastern edge of the high conductivity layer is coincident with the EKLf and the Huya fault. The electrical resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 79 publications
6
23
0
Order By: Relevance
“…In general, compared with Crust1.0 [ 30 , 31 ], obtained from active source seismic studies as well as from receiver function studies ( Figure 4 ), spatial variation of the crustal density structures and Moho boundary obtained from our gravity study is in good agreement with previous studies [ 8 , 9 , 10 , 11 , 12 , 23 , 24 , 25 , 26 ]. The similarity of interface’s depth between our model and Crust1.0 indicates the robustness of our result.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In general, compared with Crust1.0 [ 30 , 31 ], obtained from active source seismic studies as well as from receiver function studies ( Figure 4 ), spatial variation of the crustal density structures and Moho boundary obtained from our gravity study is in good agreement with previous studies [ 8 , 9 , 10 , 11 , 12 , 23 , 24 , 25 , 26 ]. The similarity of interface’s depth between our model and Crust1.0 indicates the robustness of our result.…”
Section: Discussionsupporting
confidence: 90%
“…There are several published crustal models in our study region. These models are constructed either from wide-angle deep reflection, P-wave receiver functions earthquake, surface wave tomography or ambient noise tomography [ 8 , 9 , 10 , 11 , 12 , 23 , 24 , 25 ]. The study of the P-wave receiver functions of tele-seismic data shows that multiple low-speed, low-density belts exist in the upper and middle crust below the plateau from the Bayan Har block to the central-southern Longmenshan region at depths of approximately 10~15 km and 24–45 km [ 23 , 24 , 25 ], which is consistent with the results of Aba-Wuqi deep seismic reflection profile (from project report of the geophysical exploration center, China earthquake administration).…”
Section: Crustal Model and Density Structurementioning
confidence: 99%
See 2 more Smart Citations
“…values are recovered in that region, and there are extremely low T e (<10km) in the seismogenic zone of the Jiuzhaigou earthquake, which means mechanically weak lithosphere consistent with seismic and magnetotelluric tomography results (Du et al, 2019;Riaz et al, 2019;Sun et al, 2020). The T e structure also suggested that there is a banded low T e (<40km) region stretched from the northeastern Bayan Har block to the southwestern Ordos block.…”
Section: Discussionsupporting
confidence: 68%